2020
DOI: 10.1021/acs.energyfuels.0c02699
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electromagnetic Induction Heating for CO2 Temperature Swing Adsorption on Magnetic Fe3O4/N-Doped Porous Carbon

Abstract: Temperature swing adsorption (TSA) has great potential for CO 2 capture. However, the limited energy efficiency and time-consuming procedure have impeded its applications. Herein, we provide a promising solution by in situ electromagnetic induction heating for TSA-based CO 2 capture (EMIH-CO 2 -TSA). The magnetic adsorbents are fabricated by growing magnetic Fe 3 O 4 nanoparticles in N-doped porous carbon (NPC). With a large surface area, N doping, and highly dispersed Fe 3 O 4 nanoparticles (less than 50 nm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Induction heating depends on three primary factors to control desorption rate: desorption time, gas uptake, and the SAR . During desorption, some energy is consumed by desorption enthalpy, while the rest dissipates into the gas stream. , With a larger iron oxide particle size, the heat intensity increases, and more energy is absorbed to heat the bed, especially given that 13X has a low thermal conductivity . As noted before, Fe 3 O 4 has a unique lattice structure with dual ion states, moderate adsorption capacity, and a large particle size (5 μm), which makes Fe 20 (D)/13X the most efficient magnetic sorbent with the fastest desorption rates of both C 2 H 6 and C 2 H 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Induction heating depends on three primary factors to control desorption rate: desorption time, gas uptake, and the SAR . During desorption, some energy is consumed by desorption enthalpy, while the rest dissipates into the gas stream. , With a larger iron oxide particle size, the heat intensity increases, and more energy is absorbed to heat the bed, especially given that 13X has a low thermal conductivity . As noted before, Fe 3 O 4 has a unique lattice structure with dual ion states, moderate adsorption capacity, and a large particle size (5 μm), which makes Fe 20 (D)/13X the most efficient magnetic sorbent with the fastest desorption rates of both C 2 H 6 and C 2 H 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lin et al fabricated magnetic adsorbents and developed in situ electromagnetic induction heating for CO 2 desorption. 329 The magnetic frameworks using HKUST-1 were fabricated by mechano-synthesis, where magnetic nanoparticles acted as nano heaters to desorb the adsorbed CO 2 . At a fixed target temperature of 110 °C, the energy efficiency was 79.2%, which is higher than other MISA technologies.…”
Section: Processes For Carbon Capture Using Cofs: Developments and Ch...mentioning
confidence: 99%
“…In recent times, global research has focused on enhancing conventional CO 2 absorption/adsorption and desorption/regeneration using hydrophilic/hydrophobic nanoparticles and suspensions. CNTs-TEPA-30, CNT-Ca, graphite, Fe 3 O 4 /N-doped porous carbon, and N-doped porous carbon were used as sorbents and carried out the CO 2 adsorption experiments at the temperatures of 273–313 K, and the results revealed that good sorption capacities of 3.56 mmol/g, 550 mg/g at 1123 K, 1.06, 2.64, and 5.26 mmol/g were achieved. The CNFs supported K 2 CO 3 for CO 2 capture and achieved 1.6 mmol/g CO 2 sorption capacity, and fast desorption kinetics at a low temperature of 423 K was achieved.…”
Section: Introductionmentioning
confidence: 99%